Media Pembelajaran Audio Visual dengan Teknik Role Playing dalam Mengembangkan Minat Belajar IPS pada Siswa Kelas V SD Negeri Umpanga Kabupaten Morowali - Nasrah, Nasrah; Puswiartika, Dhevy; Mahfud, Mahfud; Ratu, Bau (Jurnal Ilmiah Dikdaya, 2024)
Social studies lessons are boring learning for students because the content is rote memorization. Based on the results of initial observations, it appears that the low interest in studying social studies for class V at Baiga State Elementary School is caused by students' disinterest in delivering monotonous material, teachers have difficulty providing concrete descriptions of learning material because they do not use the right media so that students have difficulty expressing facts, and arguments to develop within the topic. In general, interest in studying social studies among these students is low. This research aims to increase students' interest in learning social studies and describe the obstacles and solutions for implementing the role playing model with audio-visual media. This classroom action research was carried out in two cycles with planning, implementation, observation and reflection stages. The research results show that the role playing model with audio-visual media can increase students' interest in learning social studies. The obstacle in implementing the role playing model with audio visual media is that it is difficult for students to be suitable in playing the role of a teacher, where students are less imbued with their role, students are less active in asking questions during activities. The solution offered is that teachers pay more attention to the abilities of students in determining the role of each student so that they are more aware of their role.